Neutron resonance transmission imaging for 3D elemental mapping at the ISIS spallation neutron source. Issue 3 (15th January 2015) - Festa, Giulia; Cippo, Enrico Perelli; Di Martino, Daniela; Cattaneo, Roberta; Senesi, Roberto; Andreani, Carla; Schooneveld, Erik; Kockelmann, Winfried; Rhodes, Nigel; Scherillo, Antonella; Kudejova, Petra; Biro, Katalin; et al.
Abstract : NRTI: a new non-destructive neutron-based technique for the image reconstruction of the bulk elemental composition. Abstract : We demonstrate for the first time the viability of a three-dimensional (3D) elemental imaging technique based on Neutron Resonance Transmission Imaging (NRTI), which is a neutron technique based on the presence of a resonance structure in the neutron-induced reaction cross sections. These resonances allow the identification of elements and isotopes within an object in a non-destructive manner. A dedicated set-up on the INES (Italian Neutron Experimental Station) beamline of the ISIS spallation neutron source was employed for the experiments. An early mediaeval disc fibula from the Hungarian National Museum in Budapest was used for our demonstration. The methodology and analysis procedures are described and the results obtained from the reconstruction of the 3D NRTI elemental image of the ancient object are compared with the results obtained from other neutron-based 3D imaging techniques.